Association of distorted eating behaviors with cardiometabolic risk indices in preadolescents. The Healthy Growth Study. (1st August 2015) - Moschonis, George; Georgiou, Alexandra; Sarapi, Katerina; Manios, Yannis
Highlights: Distorted eating is associated with increased lipid and insulin levels in adults. The current study examined this association in children. Distorted eating behavior was assessed using DEBQ and ChEAT questionnaires. "Dieting" was positively associated with LDL-c and negatively with HOMA-IR. LDL-c and HOMA-IR were also associated with "food awareness" and "food preoccupation". Abstract: The association between distorted eating behavior (DEB) with cardiometabolic risk (CMR) in children has been poorly investigated. The aim of the study was to examine the association between DEB with certain CMR indices in 9- to 13-year-old children in Greece. A cross-sectional epidemiological study was conducted among 1803 schoolchildren from 77 primary schools in 4 counties of Greece with full data on DEBQ and ChEAT questionnaires and CMR indices. Children underwent anthropometric measurements and Tanner stage, serum lipid, glucose, insulin and HOMA-IR levels assessments. Univariate and multivariate linear regression analyses were performed to test for the association between components of DEBQ and ChEAT with CMR indices. Several significant associations between components of DEBQ and ChEAT with CMR indices were observed when tested at univariate regression models in both boys and girls. However, after adjusting for several possible confounders, including Tanner stage, all significant associations were lost in girls while only a few remained in boys. Thus, DEB might have an unfavorable effect also in certain CMR indices, besides nourishment status. This is more pronounced in preadolescent boys for whom hormonal changes due to the transition to adolescence have not yet been established compared to girls. Still further research is needed to shed more light on these associations.